PENGEMBANGAN PARIWISATA BERKELANJUTAN BERBASIS ECO-EDU-SPIRITUAL-TOURISM SEBAGAI UPAYA PENINGKATAN SOSIAL EKONOMI MASYARAKAT PERKOTAAN (Studi Kasus: Tukad Bindu, Desa Kesiman, Kota Denpasar) - LUH PUTU KIRANA PRATIWI; NYOMAN YUDIARINI; I WAYAN WIADNYANA; SRI MULYANI (Universitas Mahasaraswati Mataram, 2020)
This study aims to analyze the problematic problems in regional development and determine effective alternative strategies in developing eco-edu-spiritual-tourism-based tourism. The method used is the SLA (Sustainable Livelihoods Approach) approach based on three stages of activities, namely (1) the awareness, participating, institutionalization stages along with the SWOT analysis. The results showed an alternative strategy used to model the potential for the development of urban eco-edu-spiritual-tourism as an effort to support the creative economy in the ayung tributary of Denpasar City is the SO (Strengths-Opportunity) Strategy, which is a strategy that uses power to take advantage of opportunities namely (1) Optimizing the effective use of tourist land; (2) Development of centers of economic activity and improvement of the quality of tourism products; (3) Development of eco-edu-spiritual tourism-based tourism packages as an effort to develop sustainable urban tourism. It can be suggested in research that the Government through the relevant Dinas is expected to facilitate tourism support infrastructure and involve official activities as an effort to promote Tukad Bindu as an area that has succeeded in revitalizing the clean river in urban areas so that economic improvement can be achieved significantly.